Doublecortin‐like expressing astrocytes of the suprachiasmatic nucleus are implicated in the biosynthesis of vasopressin and influences circadian rhythms. Issue 11 (3rd August 2021) - Coomans, Claudia; Saaltink, Dirk‐Jan; Deboer, Tom; Tersteeg, Mayke; Lanooij, Suzanne; Schneider, Anne Fleur; Mulder, Aat; van Minnen, Jan; Jost, Carolina; Koster, Abraham J.; Vreugdenhil, Erno
Abstract: We have recently identified a novel plasticity protein, doublecortin‐like (DCL), that is specifically expressed in the shell of the mouse suprachiasmatic nucleus (SCN). DCL is implicated in neuroplastic events, such as neurogenesis, that require structural rearrangements of the microtubule cytoskeleton, enabling dynamic movements of cell bodies and dendrites. We have inspected DCL expression in the SCN by confocal microscopy and found that DCL is expressed in GABA transporter‐3 (GAT3)‐positive astrocytes that envelope arginine vasopressin (AVP)‐expressing cells. To investigate the role of these DCL‐positive astrocytes in circadian rhythmicity, we have used transgenic mice expressing doxycycline‐induced short‐hairpin (sh) RNA's targeting DCL mRNA (DCL knockdown mice). Compared with littermate wild type (WT) controls, DCL‐knockdown mice exhibit significant shorter circadian rest‐activity periods in constant darkness and adjusted significantly faster to a jet‐lag protocol. As DCL‐positive astrocytes are closely associated with AVP‐positive cells, we analyzed AVP expression in DCL‐knockdown mice and in their WT littermates by 3D reconstructions and transmission electron microscopy (TEM). We found significantly higher numbers of AVP‐positive cells with increased volume and more intensity in DCL‐knockdown mice. We found alterations in the numbers of dense core vesicle‐containing neurons at ZT8 and ZT20 suggesting that the peak and trough of neuropeptide biosynthesis is dampened in DCL‐knockdown mice compared to WT littermates. Together, our data suggest an important role for the astrocytic plasticity in the regulation of circadian rhythms and point to the existence of a specific DCL + astrocyte‐AVP + neuronal network located in the dorsal SCN implicated in AVP biosynthesis. Main Points: DCL is expressed in GAT3+/GFAP– astrocytes that are associated with vasopressin–producing neurons in the SupraChiasmatic Nucleus. DCL knockdown results in faster adjustments to jet–lags. DCL knockdown changes the biosynthesis of vasopressin.